Ground-level insights from AgriGHALA baseline survey - Koech, Grace; Kenduiywo, Benson; Kiogora, Joseline Kanja (2025)
The Alliance of Bioversity International and CIAT, in partnership with agriBORA and with support from Partnering for Green Growth and Global Goals 2030 (P4G), launched a baseline survey on June 30th in Kenya's Uasin Gishu County and Bungoma County.